KONDISI SOSIO-HISTORIS JAZIRAH ARAB PRA-ISLAM: Sebuah Analisis Komprehensif Menjelang Turunnya Al-Qur'an - Aguspian; Andi Miswar; Sohrah Sohrah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2025)
This article presents a comprehensive socio-historical analysis of the Arabian Peninsula before the advent of Islam and the revelation of the Qur'an in the 630s CE. Based on a synthesis of archaeological evidence, ancient external records, and early Islamic historical texts, this research aims to delineate the complex and diverse social, economic, political, and religious landscape of the Arabian Peninsula. In contrast to simplified narratives that often portray this period as a monolithic "Age of Ignorance," this analysis highlights sophisticated tribal structures, dynamic economic activities including long-distance trade and established financial practices, political fragmentation marked by inter-tribal conflicts, and a broad spectrum of religious beliefs ranging from polytheism to evolving monotheism. By shedding light on regional variations in key centers such as Mecca, Medina (Yathrib), Hijaz, and Yemen, this report demonstrates how these multifaceted conditions collectively set the stage for the profound transformation brought about by Islam. Keywords: Socio-Historical, Social Structure, Economy, Politics, Religion, Culture